Professionel ledelse af professionshøjskoler – fortalt og fortolket af to rektorer - Bøje, Jakob Ditlev (Tidsskrift for Professionsstudier, 2018)
”Professional leadership” were some of the keywords when the legislation for University Colleges in Denmark was passed in 2007. In contrast to the previous institutions (seminarium and CVU), the University Colleges should be led by so-called professional leaders. But who were these leaders? Where did they come from? What sense did they make of the University Colleges and themselves as professional leaders? And what has since happened? Based on narratives told by two prominent headmasters in 2007, these questions are discussed in this article. The conclusion is that the generic leader has taken over power from the specialist leader.